Analysis of suicide tendency of the persons with physical disabilities in the context of discrimination - Nalçakar, Gizem (My University, 2020)
The main purpose of this study is to understand the patterns of suicidal behaviors of the persons with disabilities within their life conditions. The problem statement relies on how “Enforcing Normalcy” constructs a social order and discriminates the “abnormal ones” from the society. In this study, the term of “abnormal ones” refersto disabled people who are defined as reverse of being able to perform normally. Therefore, this study grounds on the binary of normal and abnormal ones in the society and how the process of these binary oppositions creates a social exclusion and leads to the tendency of suicide. The study also confirms that social exclusion and discrimination of persons with physical disabilities still exist in society. The research methods used in this study include literature review on disability, data collection from the randomly selected population, data collection, interview through “Perceived Discrimination Scale” and “Suicide Probability Scale”, and the analysis of collected data. Interviews have been conducted with persons with disabilities who got disabled by different causes. The results of the research reveal the positive relation of physical disability and suicide tendency, through the analysis of Perceived Discrimination Scale and Suicide Probability Scale points.

Bu çalışmanın öncelikli amacı, intihara eğilimli davranışlar gösteren fiziksel engelli bireylere yönelik davranış örüntülerini anlamlandırmaktır. Çalışmanın problemi, “Normalliği Dayatmak” olgusunun yarattığı sosyal düzen ile “Anormali Dışlamak” üzerine oluşturulan toplumlardır. Bu doğrultuda, çalışmada kullanılan “anormal” kavramı toplum nezdinde normal dışı davranışlar ve varoluş sergileyen engelli bireyleri yansıtmaktadır. Bu bağlamda söylenebilir ki; çalışma normal ve anormal kavramlarının yarattığı ikili çatışma ve bu çatışma sebebiyle dışlanılan bireylerin intihar eğiliminde görülen intihar eğimine yönelmektedir. Çalışma bu anlamda engelli bireylerin uğradığı sosyal dışlanma ve ayrımcılık kavramları üzerinde durmaktadır. Çalışmanın araştırma metodu, engellilik çalışmalarına odaklanan kaynak araştırması, fiziksel engelli popülasyon arasından rastgele seçilen katılımcılar ile “Algılanan Ayrımcılık Ölçeği” ve “İntihar Olasılığı Ölçeği” aracılığı ile yapılan görüşmeler ve bu görüşmelerden elde edilen verilerin analiz edilmesi olarak açıklanmaktadır. Görüşmeler, farklı sebepler ile “engelli” olarak tanımlanan bireylerle gerçekleştirilmiştir. Algılanan Ayrımcılık Ölçeği ve İntihar Olasılığı Ölçeği puanlarının incelenmesi sonucu, araştırma fiziksel engellilik durumu ile intihar eğilimi arasındaki anlamlı ve pozitif ilişki ortaya çıkarmıştır.
Tez (Yüksek Lisans) - Yıldız Teknik Üniversitesi, Sosyal Bilimler Enstitüsü, 2020
Keywords: Engellilik; İntihar; Normallik; Sosyal dışlanma; İdeal beden; Disability; Suicide; Normalcy; Discrimination; Social exclusion; Ideal body